MODERN CHALLENGES AND THREATS TO INTERNATIONAL ACTIVITIES OF UKRAINIAN ENTERPRISES - Domashenko, Maryna; Hlushchenko, Danyil; Domashenko, Valeriia (Socio-economic relations in the digital society, 2024)
At the current stage of development of the economy of Ukraine, the question of building a stable, ecological, strong national economy is quite acute. The domestic sector of the economy faced new challenges and threats caused by the full-scale invasion of Russia on the territory of Ukraine, which fundamentally complicated the international activities of Ukrainian enterprises. Therefore, research aimed at developing means of countering modern challenges and threats to the international activity of Ukrainian enterprises is gaining relevance. The article is devoted to the study of modern challenges and threats to the international activity of Ukrainian enterprises. The article examines the activities of LLC «KARNEY» a Ukrainian company operating on the international market. The work identifies the main challenges and threats for Ukrainian companies using the example of LLC " KARNEY", as well as proposed countasures to these challenges and threats in such areas as: political (the company should have a corporate lawyer on staff who will be able to better analyze the tender documentation, as well as correctly submit tender offers, correct drafting of a foreign economic agreement (contract), the presence of own trucks in the company), economic (minimization of currency risk by fixing the price in the contract in foreign currency, diversification of energy suppliers, indication of force majeure circumstances when concluding a long-term contract); cross-cultural diplomacy (to provide the opportunity for female personnel, even if they do not hold management positions, to take part in personal intertional business meetings; encourage employees to learn foreign languages); technological (introduce strategies for equipment modernization; create a storage fund at the enterprise for equipment modernization).
Keywords: Competiveness; international activities; market; international competiveness; challenges; treats; prevention measures; Ukrainian enterprises